The Comprehensive Effects of Biochar Amendments on Soil Organic Carbon Accumulation, Soil Acidification Amelioration and Heavy Metal Availability in the Soil–Rice System - Juanhua Tao; De Chen; Shaofu Wu; Qi Zhang; Wendan Xiao; Shouping Zhao; Xuezhu Ye; Tianfen Chu (Agronomy)
In recent years, biochar (BC) and biochar-based soil amendments (CSAs) have been widely used in agriculture and the environment. In the present study, a two-rice-season field study was conducted to explore the comprehensive effects of applying BC (1%) and CSA (0.5% and 1%) on soil organic carbon accumulation, soil acidification amelioration and heavy metal availability in a soil–rice system. The results show that soil pH was increased by 0.5–1.7 units and 0.3–1.0 units, respectively, in the early rice season and late rice season treated by the amendments compared with CK. Soil organic contents were increased by 18–30% in the early rice season and by 15–25% in the late rice season in the amended treatments. In addition, soil available phosphorus contents were largely increased as a result of BC and CSA addition. Soil CaCl2 extractable heavy metals (Cd, Ni, Cu and Zn) were simultaneously decreased by BC or CSA amendments. In addition, Cd contents in early rice grain and late rice grain were significantly reduced by 25–48% and 52–83% in amended treatments, while Zn contents were generally not affected. The uptake of Cu and Ni was also decreased by BC and CSA. This study demonstrates that biochar application alone or combinates with inorganic amendments (limestone, sepiolite and potassium dihydrogen phosphate) can significantly improve soil properties and nutrient content and decrease the heavy metal (especially for Cd and Ni) uptake and accumulation from soil to rice grain, where the combination application is more effective.